Examining the relationship between post-stroke cognitive dysfunctions and mood disorders in hospitalised Saudi patients - Alarjan, Sami (2016)
Background: The Ministry of Health in Saudi Arabia estimates that there are at least 20,000 strokes per year across the country (126/100,000) and approximately half of those with stroke may develop cognitive dysfunction or mood disorders. However, a review of the literature revealed that research in the area of post-stroke cognitive dysfunction and mood disorders in the Kingdom of Saudi Arabia (KSA) is severely lacking. Accordingly, these studies aimed to bridge the knowledge gap with an emphasis on three central aspects. The first aim was to assess the prevalence of post-stroke cognitive dysfunctions in the KSA population using neuropsychological tests. The second aim was to assess the prevalence of post-stroke mood disorders in the KSA using self-report scales. The third aim was to evaluate the relationship between cognitive dysfunctions and mood disorders.